THE USE OF GUIDED LEARNING CELL TECHNIQUE TO DEVELOP ACTIVE COLLABORATION OF IXA STUDENTS OF SMP NEGERI 2 SEMARANG IN WRITING REPORTS - Farida, Diana (Language Circle: Journal of Language and Literature, 2012)
The competence of writing English texts has become very important in this global era. To facilitate junior high school students to gain the competence, English teachers employ various techniques to reach the goal with the curriculum as the guideline. The research was conducted by employing Guided Learning Cell (GLC) technique. The objectives of this study are (1) to investigate to what extent GLC technique can develop the competence of the IX A students of SMPN 2 Semarang to write reports and (2) to investigate to what extent GLC technique can develop active collaboration of the IX A students of SMPN 2 Semarang inÃÂ  writing reports. The research was conducted through Action Research with two cycles. Each cycle consists of planning, acting, observing and reflecting. The results of the research can be concluded as follows: (1) GLC technique applied during the research had successfully developed studentsÃ¢â¬â¢ writing report competence. Before the research, IX A studentsÃ¢â¬â¢ writing average score is 70.52, while at the end of the research it is 84.29. At the end of the research, the average score has exceeded the writing passing grade, 80. This proved that the technique had developed their writing competence to the extent of 13.77. (2) Based on the second requirement of the research, GLC technique could also successfully develop studentsÃ¢â¬â¢ active collaboration with their mates to the extent of 42%. Before the research, only 1 (4%) student who could gain the passing grade, while Ã¢â¬â at the end of the research - 21 (88%) students could do so.